2023
DOI: 10.1001/jamanetworkopen.2023.3652
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain, Burnout, and Suicidal Ideation in Tenured University Hospital Faculty Staff in France in 2021

Abstract: ImportanceThe ability to attract and retain university hospital faculty staff is in jeopardy because of the high levels of mental symptoms in this professional group.ObjectiveTo examine the prevalence and determinants of symptoms of severe burnout, job strain, and suicidal ideation in tenured associate and full professors in university hospitals.Design, Setting, and ParticipantsThis nationwide cross-sectional study offered online surveys to 5332 tenured university hospital faculty members in France from Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This result is particularly worrying, considering that mental health problems impact doctors of all categories and all ages in France. In a recent study involving 2,390 French teaching hospital physicians, almost 40% of respondents reported severe burnout, and 12% experienced job strain ( Dres et al, 2023 ). A 2019 meta-analysis estimated the prevalence of burnout at 49% among French doctors, and at 52% among residents ( Kansoun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is particularly worrying, considering that mental health problems impact doctors of all categories and all ages in France. In a recent study involving 2,390 French teaching hospital physicians, almost 40% of respondents reported severe burnout, and 12% experienced job strain ( Dres et al, 2023 ). A 2019 meta-analysis estimated the prevalence of burnout at 49% among French doctors, and at 52% among residents ( Kansoun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impact of psycho-social risk factors, workplace stress and violence, has been identified as crucial determinants of psychological wellbeing ( Rugulies et al, 2023 ) in particular in the healthcare sector ( Hu et al, 2019 ; Kansoun et al, 2019 ; Dres et al, 2023 ). The overall proportion of healthcare workers who report experiencing violence at work has been estimated to reach nearly 80% ( Rossi et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, work-related stress is a significant predictor of suicidal cognition (24). Job stressors are determinants of common mental disorders and are associated with an elevated risk of suicidal ideation and behaviours (46), and there is a relationship between job strain, burnout, and suicidal ideation among workers in the healthcare sector (47). Kabir et al (48) found a significant association between workplace bullying and burnout, and nurses' suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…The poem’s devastating last line seems a warning to us to do more: the burnout implied in the dispirited “Some of us cry. All of us get back to work.” may be itself a risk factor for suicidal ideation and demands care and attention from our colleagues and workplaces, not least the opportunity to speak and write about experiences of powerlessness.…”
mentioning
confidence: 99%